PERAN KEPALA SEKOLAH DALAM MENCIPTAKAN BUDAYA RELIGIUS PADA SMP MUHAMMADIYAH 4 BANJARMASIN - Imaniah Elfa Rachmah (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
The role of the principal is crucial in creating a religious culture in an educational institution. Religious culture in school can be created when the principal performs his function an administrator. The importance of building a religious culture in school is primarily concerned with achieving the goals of school education. The leadership of the principal is part of a very important management function to achieve educational goals in schools. Leadership can play a role in protecting some of the issues of inappropriate organizational setting, including in this case in creating a religious culture, such as; the distribution of power that blocks the effective course of action, the lack of resources, the perceived poor procedure and so on, the fundamental school problems. Religious culture can be known from the regularity of behaving like religious activities held school, the language used that contains religious cultural values, norms that contain the standards of behavior of school residents, the formation of student personality quality both in science and moral, besides that religious culture can also be seen from the school rules made by the principal. Keywords: Role of Principal, Religious Culture